2022
DOI: 10.1093/mnras/stac1636
|View full text |Cite
|
Sign up to set email alerts
|

Linking the brightest stellar streams with the accretion history of Milky Way like galaxies

Abstract: According to the current galaxy formation paradigm, mergers and interactions play an important role in shaping present-day galaxies. The remnants of this merger activity can be used to constrain galaxy formation models. In this work we use a sample of thirty hydrodynamical simulations of Milky Way-mass haloes, from the AURIGA project, to generate surface brightness maps and search for the brightest stream in each halo as a function of varying limiting magnitude. We find that none of the models shows signatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
(96 reference statements)
0
4
0
1
Order By: Relevance
“…Many of these systems are predicted to be detectable in LSST. In addition, these imaging surveys will uncover populations of stellar streams around external galaxies (e.g., Pearson et al 2019;Vera-Casanova et al 2022) and enable similar tests with a larger sample of galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these systems are predicted to be detectable in LSST. In addition, these imaging surveys will uncover populations of stellar streams around external galaxies (e.g., Pearson et al 2019;Vera-Casanova et al 2022) and enable similar tests with a larger sample of galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…Stellar halos of Milky Way-like galaxies have become objects of interest in the astronomical community, and various studies regarding them have been carried out in recent years (e.g., Zolotov et al 2009;Cooper et al 2010;Tissera et al 2014;Peacock et al 2015;Monachesi et al 2016aMonachesi et al , 2016bRey & Starkenburg 2022;Vera-Casanova et al 2022). These halos can be considered to be a consequence of the hierarchical formation of structures of the ΛCDM model (Searle & Zinn 1978;Frenk et al 1988;Navarro et al 1997) because stars can be found in the external regions of these massive galaxies, principally due to the interactions between subhalos.…”
Section: Introductionmentioning
confidence: 99%
“…Past mergers also leave behind a morphological record in the form of various post-merger features, which can be the result of major mergers-which is typically the case for plumes (e.g., Lauer 1988) and tidal tails (e.g., Pfleiderer 1963;Toomre & Toomre 1972)-or minor mergers, which usually produce streams (e.g., Johnston et al 1999) or shells (e.g., Malin & Carter 1983;Quinn 1984). By examining these signatures, it is possible to infer a galaxy's recent interaction history and thereby disentangle the role of various merging processes governing galaxy properties (e.g., Johnston et al 2008;Martínez-Delgado et al 2009;Spavone et al 2020;Vera-Casanova et al 2022).…”
Section: Introductionmentioning
confidence: 99%